تحليل المجاز المرسل على موضوع الحب والمرأة في ديوان الشعر أشهد أن لا امرأة إلا أنت لنزار قباني - Ismail Ageng Hutomo, Muhammad; Edy Setyawan, cahya (Journal of Arabic Language and Literature (ALLAIS), 2022)
The formulation of the problem in this thesis is how to use the types and meanings of the mursal figure of speech contained in the poem asyhadu alam roata ila anti. The purpose of this study is to find out how the types and meanings of the mursal figure of speech are used in the poem asyhadualam roata ila anti. This research uses the type of library research. The researcher used the primary data source of Nizar Qabbani's diwan ashhadu alam roata ila anti. The method used in this study is a descriptive stylistic qualitative method. In this study, researchers used the technique of collecting data documentation. And use the reading persistence technique in the data validity technique. The researcher found several sentences containing majaz mursal in Nizar Qabbani's diwan ashhadu alam roata ila anti as many as sixty-two sentences. Then this majaz is divided into eight parts, namely kulliyah-juz'iyyah, sababiyyah-musabbabiyyah, i'tibar ma kaana-i'tibar maa sayakuunu, haaliyyah-mahalliyah. As for kuliyyah there are five sentences and juz'iyyah four sentences. As for sababiyyah six and musabbabiyyah twenty sentences. As for i'tibar maa kana there are two sentences and i'tibar maa sayakuunu two sentences. The haaliyyah is nine and the mahalliyyah is fourteen sentences